2005
DOI: 10.1111/j.1469-0691.2005.01127.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility testing of Mycobacterium tuberculosis: comparison of the BACTEC TB-460 method and flow cytometric assay with the proportion method

Abstract: Tuberculosis is a leading cause of morbidity and mortality worldwide. Susceptibility testing of the causative agent, Mycobacterium tuberculosis, is critical for control of the disease. This study compared the flow cytometric susceptibility assay with the proportion method and the BACTEC TB-460 system. There was agreement between the flow cytometric and proportion methods for 73 (94%) of 78 isoniazid tests, and complete agreement for 26 ethambutol and rifampicin tests. In contrast, the proportion and BACTEC met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…A flow cytometer can make sensitive and precise measurements of light scattered or emitted by individual cells at a dozen or more different wavelengths, even though the cell images obtained are typically not in focus. Based on prior experience with both flow and image (105, 106) cytometry, and more recent theoretical (11) and experimental (12) work, we concluded that it should be possible to build a small, robust, energy‐efficient, and extremely inexpensive fluorescence image cytometer that could perform essentially the same measurements now done for TB diagnosis by laser scanning cytometry (72) and automated microscopy (76, 77) and for rapid (24–48 h) antimicrobial susceptibility determination of MTB by flow cytometry (71, 94–104).…”
Section: A Minimalist Fluorescence Image Cytometer For Resource‐poor mentioning
confidence: 98%
See 1 more Smart Citation
“…A flow cytometer can make sensitive and precise measurements of light scattered or emitted by individual cells at a dozen or more different wavelengths, even though the cell images obtained are typically not in focus. Based on prior experience with both flow and image (105, 106) cytometry, and more recent theoretical (11) and experimental (12) work, we concluded that it should be possible to build a small, robust, energy‐efficient, and extremely inexpensive fluorescence image cytometer that could perform essentially the same measurements now done for TB diagnosis by laser scanning cytometry (72) and automated microscopy (76, 77) and for rapid (24–48 h) antimicrobial susceptibility determination of MTB by flow cytometry (71, 94–104).…”
Section: A Minimalist Fluorescence Image Cytometer For Resource‐poor mentioning
confidence: 98%
“…A series of studies (94–101) published since 1995 by Ronald Schell and his colleagues at the University of Wisconsin established that flow cytometry can be used to determine susceptibility of MTB to all first‐line and several second‐line drugs within 24–36 h; other groups (71, 102–104) have obtained similar results. Reis et al (103) noted that their work was entirely done in a developing country (Brazil).…”
Section: Determination Of Antimicrobial Susceptibility In Tbmentioning
confidence: 99%
“…Alternative dyes and flow cytometry methods have been assessed for their utility in measuring the viability of mycobacterial species and for testing antibiotic activity against M. tuberculosis but have not been routinely adopted ( 14 ). Previously, antibiotic susceptibility testing has been demonstrated with the use of other metabolic dyes, such as 5-chloromethylfluorescein diacetate (FDA) ( 15 ). Syto 16 is a nucleic acid stain that more readily penetrates dead cells than other dyes and was formerly used to study the growth cycle of Mycobacterium avium ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of flow cytometry-based DSTs were performed against M. tuberculosis , while these have been previously tested only to a limited extent against NTM. The first flow cytometry methods based on the principle that treated tuberculous and nontuberculous mycobacteria hydrolyze significantly less fluorescein diacetate to free fluorescein than non-treated bacteria, which therefore demonstrate less intensity of fluorescence [ 75 , 76 , 77 , 78 ]. The strength of these assays is to provide results within 24 h, thanks to the fact that they did not require multiplication of the mycobacteria.…”
Section: Flow-cytometry-based Drug Susceptibility Testingmentioning
confidence: 99%